STRATEGI PENDIDIKAN ISLAM DI ERA DIGITAL - NURYADIN NURYADIN (Fitrah: Jurnal Kajian Ilmu-Ilmu Keislaman, 2017)
This paper aims to present the strategy of Islamic education in the digital era. The digital era has brought about many changes in various aspects of human life, including in Islamic education. Islamic education as a subsystem of national education needs to deal with and implement the comprehensive measures and sustainable, in scrutinizing the various opportunities and challenges of the digital era in order to establish the existence and role to give birth to a superior generation in intellectual, spiritual, moral, and social as well as creative